Estimasi Simpanan Karbon Tegakan Menggunakan Citra Sentinel-2A Pada Kawasan Mangrove Labuan Tereng Kabupaten Lombok Barat: Estimation of Standing Carbon Stock Using Sentinel-2A Imagery in the Labuan Tereng Mangrove Area West Lombok Regency - Moh Rodiansyah Hambali; Andi Chairil Ichsan; Niechi Valentino; Andrie Ridzki Prasetyo (LPPM Universitas Mataram, 2023)
The primary worry in addressing climate change problems is the elevation in global temperatures resulting from the growing levels of CO2 emissions in the atmosphere. Mangrove ecosystems contribute to the